Análise multicritério aplicada à avaliação do sistema de ensino adotado nas escolas públicas estaduais do Rio de Janeiro - Meca, Eduardo Fernando Moreira (2006)
The present work searches the classification problem of the education system adopted in States Public Schools, done by the Education State Secretary (SEE/RJ), through the Programa Nova Escola . This investigation considers the fundamentals of the Multiple Criteria Decision Aid MCDA applies to the set of criterion (indicators) adopted by the Programa Nova Escola of the Secretaria de Estado de Educação RJ. The concepts of the MCDA get been developed to deal with problems that involve multiples criterions and subjects analysis. Furthermore than the propose application, a practical case will be shown and analyzed at the end of this study, resulting in an comparison among the classifications obtained with the BORDA methods, CONDORCET, ELECTRE I, ELECTRE II and the classification obtained with the Programa Nova Escola